THE STUDY OF NOUN FOUND IN SHAWN MENDES’ SONG ENTITLED LOST IN JAPAN - Safitri, Alin; Parmawati, Aseptiana (IKIP Siliwangi, 2021)
Descriptive qualitative method is used in this study. This study aimed to investigate nouns and the variety of nouns found in a song entitled Lost in Japan by Shawn Mendes. In collecting the data, the researchers applied three steps, namely selecting one song to be examined, read and elaborate the song lyrics to discover nouns, and classify nouns based on the types. Based on the data analysis, the researchers discovered 16 nouns with seven types of nouns. All nouns can be indicated to more than one type. The results are summarized as follows; 15 common nouns, 1 proper noun, 11 abstract nouns, 5 concrete nouns, 12 countable nouns, 4 uncountable nouns, and 4 compound nouns.Â Keywords:Â Noun, Song lyrics, Types of noun